2008
DOI: 10.1074/jbc.m705943200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-7a Modulates the Synaptic Vesicle Cycle and Synaptic Transmission in Hippocampal Neurons

Abstract: Wnt signaling is essential for neuronal development and the maintenance of the developing nervous system. Recent studies indicated that Wnt signaling modulates long term potentiation in adult hippocampal slices. We report here that different Wnt ligands are present in hippocampal neurons of rat embryo and adult rat, including Wnt-4, -5a, -7a, and -11. Wnt-7a acts as a canonical Wnt ligand in rat hippocampal neurons, stimulates clustering of presynaptic proteins, and induces recycling and exocytosis of synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
224
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(238 citation statements)
references
References 47 publications
12
224
2
Order By: Relevance
“…This result suggests that Wnt7a regulates spine number indirectly by increasing the number of presynaptic release sites, which could then stimulate spine formation. Previous studies have reported that Wnt7a does not affect the postsynaptic side (23,40). This apparent discrepancy with our results could be due to the different sources of Wnt7a used (23,40).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This result suggests that Wnt7a regulates spine number indirectly by increasing the number of presynaptic release sites, which could then stimulate spine formation. Previous studies have reported that Wnt7a does not affect the postsynaptic side (23,40). This apparent discrepancy with our results could be due to the different sources of Wnt7a used (23,40).…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have reported that Wnt7a does not affect the postsynaptic side (23,40). This apparent discrepancy with our results could be due to the different sources of Wnt7a used (23,40). Importantly, here we show that postsynaptic activation of Wnt signaling through Dvl1 expression promotes spine growth and excitatory synaptic transmission.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In fact, we found that Wnt/b-catenin modulates the synaptic vesicle cycle and synaptic transmission in rat hippocampal neurons, 76 and non-canonical Wnt signaling also modulates PSD-95 clustering. 33 Therefore, these possible mechanisms needed to be explored in APP-PS1 animals treated with lithium and rosiglitazone.…”
Section: Discussionmentioning
confidence: 91%
“…Wnt signals to both sides of the synapse to induce synaptic assembly in the CNS. In axons, Wnts activate a canonical Wnt signaling pathway that requires inhibition of Gsk3 (Ahmad-Annuar et al, 2006;Cerpa et al, 2008b;Davis et al, 2008). On dendrites, Wnts trigger the recruitment of postsynaptic components through the activation of noncanonical pathways (Farías et al, 2009;Cuitino et al, 2010;Ciani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%